Liberdade de expressão em democracias: discursos e sujeitos em redes de comunicação - Oliveira, Hulda Gomides (Universidade Federal de São Carlos, 2019)
In this research we develop an analysis of discourses on freedom of expression constructed in different historical moments (antiquity, modernity and contemporaneity), trying to understand how discursive processes constitute subjectivities in democracies. Thus, we are interested not in a study of the occurrence of the terms "freedom of expression", but rather a discursive diagnosis, in the wake of Michel Foucault, of the dynamics raised in diverse conditions of "free expression", which emerged historically, names: freedom of speech, freedom of communication, freedom of ideas and opinions, freedom of thought and expression. We have seen that, because of their socio-political nature, they are discourses crossed by a series of other elements that constitute contemporary practices of "free expression", such as: a Western political philosophy, with paradigms about what the subject is and what he can express; subjects that are marked by conditions of a democratic regime and "possessors" of constitutional rights; marked by the very conditions of operation of the communication networks in which they are involved, either by the architecture of these networks, which allows practices according to a given spatial arrangement, or by dynamics that at the same time make express and silence. Thus, we consider some common places important for the construction of these discourses, and from this we form our corpus of analysis: first, the Greek agora, with the happening of the polis, considered as the place in which it would be the "free citizen to expressing "- for this, we analyze two texts, Aristotle's Politics, and Pericles' Prayer for the Dead; secondly, modern France, with the event of the French Revolution, which through the Declaration of the Rights of Man and Citizen (material we have analyzed), with a manifestly universal claim, would have won the freedom for the "people to express themselves"; Finally, contemporaneity, which with the event of the creation of social networks, on digital platforms, would be experiencing the democratic apogee of which, now, "anyone can express itself" - in this cut, we analyzed statements inscribed on the Internet, as cyberspace of free expression. For us, this trajectory crosses and constitutes the subjects that express themselves in the social networks of the present, and, precisely considering this, is that we are interested in understanding the formation and the operation of such discursive practices to deconstruct any sacralization of freedom of expression in democracies, either of subjects who express themselves in the name of the city, in the name of men's rights, or in their own name. In order to develop such an approach, we take as an analytical clipping of the present, statements that circulate in Brazil in materialities of Facebook (pronounced as "pronto" and "mimimi"), considering the issue of great circulation in the country at the beginning of the 21st century. Finally, as far as our theoretical perspective is concerned, we assume the parameters of Foucaultian archeogynealogy (as we discussed throughout the text), by enabling us to analyze the relationships between ancient and modern practices that end up objectifying and subjecting the subjects who express themselves in the social networks of the present time, composing, finally, whether by regularities or discontinuities, practices and statements about freedom of expression in the contemporary, through processes of objectification and subjectivation.
Liberté d'expression dans les démocraties: discours et sujets dans les réseaux de communication
Keywords: Liberdade de expressão; Discurso; Sujeito; Redes sociais; Freedom of speech; Discourse; Social networks; Liberté d‟expression; Discours; Sujet; Réseaux sociaux; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA